Association of Undernutrition and Neonatal, Infant and Under-5 Mortality: Evidence from 62 Low-Income and Middle-Income Countries. (29th May 2020) - Ssentongo, Paddy; Lewcun, Joseph; Ssentongo, Anna; Ba, Djibril; Fronterre, Claudio; Ericson, Jessica; Gernand, Alison; Wang, Ming; Du, Ping; Chinchilli, Vernon; Schiff, Steven
Abstract: Objectives: During the Millennium Development Goals (MDG) era, many low- and middle-income countries (LMICs) failed to achieve the MDG 4 of reducing neonatal, infant, and under-5 mortality. In this study, we aimed to assess whether reductions in early childhood undernutrition is associated with a reduction in neonatal, infant and under-5 mortality rate in LMICs. Methods: We analyzed demographic and health household survey data from 62 LMICs collected between 2006 and 2018. The sample consisted of nationally representative cross-sectional surveys of children aged 0–59 months ( n  = 600, 390). We examined country-level prevalence of stunting, wasting and underweight (based on z scores < −2 per the WHO Growth Standard) each as predictors of neonatal, infant and under-5 mortality incidence using multivariate Poisson regression models adjusted for country-level mean duration of breastfeeding and gross domestic product per capita. We also examined the association between breastfeeding and mortality. Results: Overall, 28.4% (95% CI: 26.3%, 30.7%) of young children were stunted, 5.4% (95% CI: 4.5%, 6.6%) were wasted, 12.3% (95% CI: 10.4%, 14.6%) were underweight. Per 1000 live births, neonatal mortality was 23.6 (95% CI: 19.3–27.1), infant mortality was 43.4 (95% CI: 30.2–50.1) and under-5 mortality was 61.6 (95% CI: 55.3- 68.3). At the country level, a 10-fold decrease in stunting was associated with a relative risk (RR) of 0.81 (95% CI 0.66–0.98; P  < 0.001) for neonatal mortality, 0.66 (95% CI 0.55–0.80; P  < 0.001) for infant mortality, and 0.63 (95% CI 0.52–0.76; P  < 0.001) for under-5 mortality. No association was seen between wasting or underweight and child mortality. Breastfeeding was associated with lower rates of child mortality. A one standard deviation (16 months) increase in breastfeeding was associated with a RR of 0.86 (95% CI 0.76–0.97; P  = 0.015) for neonatal mortality, 0.79 (95% CI 0.70–0.89; P  < 0.001) for infant mortality, and 0.75 (95% CI 0.67–0.85; P  < 0.001) for under-5 mortality. Conclusions: In a very large, multi-country sample of nationally-representative surveys in LMICs, stunting was strongly associated with child mortality from birth to 5 years. Stunting should be a focus in the effort to achieve the Sustainable Development Goal 3.2 target to reduce neonatal and under-5 mortality in all countries by 2030. Funding Sources: National Institute of Health.